Determination of In vitro antimicrobial activity of homeopathy medicines - Mokarroma, Soyoda; Shammi, Tahmina (Stamford Journal of Microbiology, 2019)
Homeopathy is a popular alternative medicine. The mechanism of action of homeopathic drug has not been clarified but it has been found to be effective against various diseases including diarrhea, dysentery, otitis media, eczema and even cancer. After qualifying thorough investigation, it can be used against antibiotic tolerance and multi drug resistant bacteria. In a recent study, bactericidal effect of homeopathic remedies has been investigated. But such an effect is not in accordance with the general principles of homeopathy. To test this paradigm, in vitro antimicrobial effects of four homeopathic drugs Aconite 30, Arsenicum album 30, Mercuric corrosivus 30 and Mercury solution 200 against five common intestinal pathogens, including- Escherichia coli, Klebsiella sp., Salmonella sp. Pseudomonas sp., and Bacillus sp have been observed. Standard agar well diffusion technique and macrodilution technique were followed. But, tested homeopathic drugs did not show any significant effect on any of the five pathogens. Rigorous study against other organism is required to fully understand antimicrobial activity and other mechanism of action. Stamford Journal of Microbiology, Vol.8(1) 2018: 7-9